One year mortality after pediatric hydrocephalus treatment: a comparative analysis of endoscopic third ventriculostomy and ventriculoperitoneal shunt - Alali, Ahmad; Alkabouni, Wesam; Aretz, Viktoria; Volpert, Timo; Makanjira, Yollam; Kampeni, Martin; Kapapa, Thomas; Kamalo, Patrick (Frontiers in Surgery, 2025)
BackgroundManagement options for hydrocephalus have increased to include endoscopic third ventriculostomy with or without choroid plexus cauterization (ETV ± CPC) in addition to traditional ventrikuloperitoneal shunting (VPS). This study evaluates the mortality and complications of these procedures in pediatric hydrocephalus, offering insights for clinical decision-making in a low-income country context.MethodsWe retrospectively reviewed the operating theatre registry for infants under 1 year of age who underwent initial hydrocephalus surgery in a tertial sub-Saharan hospital in 2021. Follow-up was conducted for up to 1 year after surgery, confirming the patient's vital status (alive or dead) through hospital visits, contact information, and medical records. Descriptive analyses evaluated outcomes (mortality and complications), and survival was assessed using the Kaplan–Meier method with log-rank testing.ResultsA total of 127 patients were included, with 71 males (55.91%). Complete 1-year follow-up data was available for 94 (74%) patients. Of these, 35 (37.23%) underwent ETV ± CPC and 59 (62.77%) underwent VPS. The one-year survival rate was 80% (95% CI: 66.75%–93.25%) for those treated with ETV ± CPC as a definitive treatment and 78% (95% CI: 67.43%–88.57%) for those who received VPS. There was no statistically significant difference in survival rates between the two groups (Log-Rank test p = 0.809). Shunt sepsis occurred in 6 patients (10.16%, 95% CI: 2.45%–17.87%). The majority of surgical complications occurred within the first 3 months following surgery, including shunt dysfunction in 4 VPS patients (6.7%, 95% CI: 0.32%–13.08%) and failed ETV in 10 patients (22.2%, 95% CI: 8.43%–35.97%) of those who underwent primary ETV.ConclusionETV ± CPC and VPS demonstrated similar survival rates, with no significant statistical difference between the two methods. However, ETV ± CPC failure often required conversion to VPS, highlighting the importance of managing shunt-related complications like sepsis and dysfunction. Careful post-operative monitoring is essential for both procedures.